2016
DOI: 10.1002/jobm.201500533
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Bacillus megaterium YB3 from an effluent contaminated site efficiently degrades pyrene

Abstract: Industrial effluents contaminated sites may serve as repositories of ecologically adapted efficient pyrene degrading bacteria. In the present study, six bacterial isolates from industrial effluents were purified using serial enrichment technique and their pyrene degrading potential on pyrene supplemented mineral salt medium was assessed. 16S rRNA sequence analysis showed that they belong to four bacterial genera, namely Acinetobacter, Bacillus, Microbacterium, and Ochrobactrum. Among these isolates, Bacillus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In contrast, an anaerobic microorganism uses carbon to produce methane, hydrogen sulphite, nitrogen gas, and biomass (Mohanan et al, 2020). Different studies have reported the use of non-carbonaceous media such as Bushnell Hass broth, minimum salt medium, and other synthetically designed media for the isolation and characterization of specific microbes (Zahra et al, 2010;Meena et al, 2016;Park and Kim, 2019).…”
Section: Biodegradationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, an anaerobic microorganism uses carbon to produce methane, hydrogen sulphite, nitrogen gas, and biomass (Mohanan et al, 2020). Different studies have reported the use of non-carbonaceous media such as Bushnell Hass broth, minimum salt medium, and other synthetically designed media for the isolation and characterization of specific microbes (Zahra et al, 2010;Meena et al, 2016;Park and Kim, 2019).…”
Section: Biodegradationmentioning
confidence: 99%
“…In contrast to traditional approaches, the utilization of microorganisms found to be efficient to degrade recalcitrant, mutagenic, or xenobiotic compounds like polyaromatic hydrocarbons, phenols, pesticides, azo dyes, etc. (Christian et al, 2005;Meena et al, 2016;Narwal and Gupta, 2017). Similarly, other reports also have shown the microbiome's ability to degrade plastics in an economical and environment-friendly manner.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, one of the most popular strains is gordonia , a Gram-positive aerobic organism, many kinds of which are isolated from environments such as contaminated soil, wastewater, estuary sand, mangrove rhizosphere, oil-producing wells, biofilters, and activated sludge, as well as from clinical samples. Many of them are excellent in degrading environmental pollutants, alkylpyridines, phthalates, xenobiotic compounds (e.g., 1,3,5-triazines), or slowly biodegradable natural polymers (e.g., rubber) , as well as in transforming or synthesizing organic compounds (e.g., SACs), microbial surface active compounds, and carotenoids. Because of the ability to degrade refractory pollutants and synthesize organic compounds, these bacteria are potentially useful for environmental and industrial application in the last few years. , …”
Section: Introductionmentioning
confidence: 99%
“…At a lower temperature, the enzyme activity could be decreased, resulting in a slow microbial metabolism, followed with a poor phenol degradation ability. The phenomena have been reported that the removal ability of microorganisms to pollutants became deteriorative when the temperature was too low or too high (Meena et al 2016;Satapute & Kaliwal 2016;Deng et al 2018). Most wastewater treatment plants typically operate at temperatures between 0 and 30 °C, and for the microbial activity used to degrade wastewater, its degradation capacity is extremely limited at certain temperatures (Li et al 2010).…”
Section: The Optimization Of Culture Conditions For Zwb3mentioning
confidence: 99%